Borana cattle herds: Productivity, constraints and possible interventions - Assefa, M. (1990)
The 30 ollas (encampments) studied included a total of 633 families of these. 113 were classified as wealth, 200 as middle and 320 as poor. Wealthy families had three and seven times the number of cattle as middle class and poor households. Female cattle comprise the majority of the herd among all families and account 74% of the total herd on the average. Calves of poor families get less milk from their dams than do calves of weathier families get less milk from their dams than do calves of weathier families. This is because milk taken for human use varies only slightly among wealth class, while total milk production is much depressed among cows of poor families are nutritionally disadvantaged during the first year of their lives as compared to other calves. This perhaps conditions them for reduced reproductive success even though they may recover in terms of size and age at which reproductive begins. Calf mortality was higher in the herds of the intermethate wealth category. The high rate among claves of calves of poor families is wealthy families it may arise from low management input resulting from high ratio of livestock to people. In general cattle production performances are reasonable. However the high calf mortality rate requires immediate attention. Attempts to improve long-term production parameters (growth, time to pubery, claving interval etc.) may be risky in an environment characterized by risk and uncertainty. However interventions with predictable results such as mortality mitogation of calves are economically feasible for adoption by pastoralists. Reduced calf mortality through improved feeding and health care need to be compensated by increased animal offtake to promote sustainability of rengeland resources.